Analysis of tribochemical decomposition of two imidazolium ionic liquids on Ti–6Al–4V through Mechanically Stimulated Gas Emission Spectrometry. (October 2016) - Nevshupa, R.; Conte, M.; del Campo, A.; Roman, E.
Abstract: Mechanochemical degradation of imidazolium bis(trifluoromethanesulfonyl)imide room-temperature ionic liquids (RTIL) with alkyl and mPEG side groups on Ti–6Al–4V substrate was studied through analysis of gas triboemission and Raman spectroscopy. In vacuum the RTIL with longer mPEG chain had better lubricity due to its higher capacity for tribochemical passivation. Raman spectroscopy showed possible bonding of fluorine to the substrate. Mechanical stimulus caused degradation of both anionic and the cationic moieties that further reacted with the substrate and with each other. The relevant decrement of water content during rubbing was found attributable to the proper RTIL and not only to the absorption on the substrate. No volatile sulphur compounds were found supporting the hypothesis of their bonding to Ti substrate. Graphical abstract: Highlights: Direct probing of tribochemical decomposition of imidazolium ionic liquids. Side groups detachment from the cation and CF3 detachment from the anion. No emission of sulphur oxide in positive ion mass-spectra. Depolymerisation of mPEG.